2019
DOI: 10.1186/s42269-019-0209-4
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological study of invasive and non-invasive Entamoeba spp. in experimental rats

Abstract: Background: The genus Entamoeba has many species that are invasive or non-invasive (E. histolytica, E. dispar, and E. moshkovskii).The invasive E. histolytica is the main pathogenic amoeba in human. Amoebiasis involves several stages starting with the adherence of the parasite to the intestinal epithelium, followed by degradation, tissue invasion, and distribution to other organs. Results: The current study investigates the pathological changes of Entamoeba spp. infection in both rectum and cecum of experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The age of cancer patients who has parasitic infection with E. histolytica that were also checked based on the requirements of the current study and the statistical analysis showed a significant difference as explained in table (4), where the high rate of parasitic infection was reported among cancer patients with (51-60) age group while the low rate of parasitic infection was reported among (21-30) age groups of cancer patients . χ 2 = 135.58 df = 6 P-value = 0.00 S: significant differences P≤ 0.05…”
Section: Table (3): Distribution Of E Histolytica (Iga) Among Cancer ...mentioning
confidence: 85%
See 1 more Smart Citation
“…The age of cancer patients who has parasitic infection with E. histolytica that were also checked based on the requirements of the current study and the statistical analysis showed a significant difference as explained in table (4), where the high rate of parasitic infection was reported among cancer patients with (51-60) age group while the low rate of parasitic infection was reported among (21-30) age groups of cancer patients . χ 2 = 135.58 df = 6 P-value = 0.00 S: significant differences P≤ 0.05…”
Section: Table (3): Distribution Of E Histolytica (Iga) Among Cancer ...mentioning
confidence: 85%
“…The invasive E. histolytica is the main human zoonotic amoeba. The parasite must stick to the intestinal epithelium, which is caused degradation, then penetrate the tissue and spread to other organs (4). Children who live in developing countries, diarrhea is the biggest killer, accounting for 9% of all deaths in children under the age of five (5).…”
Section: Introductionmentioning
confidence: 99%